Efficacy of Annona reticulata L. Seed Extract in Callosobruchus maculatus in the Laboratory - Siahaya, Victor G (Universitas Pattimura, 2023)
Extracts from the Annona muricata plant parts are known to have a broad-spectrum insecticidal potential against various species of insect pests. This study aimed to study the bioactive compounds of Annona reticulata fruit extract against Callosobruchus maculatus in the laboratory. The study used five extract treatments that were repeated three times. The treatment consisted of formulations with concentrations of 0.135%, 0.182%, 0.246%, 0.331%, and 0.450%, and controls. The test was carried out by the residual method on the petri dish and tested on the female insect C. maculatus, as well as testing the content of metabolites in the seeds. Phytochemical test results showed that A. reticulata seeds contain alkaloids, phenolics, flavonoids, tannins, steroids, and saponins. The results showed that paralysis already occurred as early as 1 day after treatment (dat) for all given concentrations of the extract, and the death of test insects tended to increase from the lowest concentration to the highest concentration. The mortality of test insects also tends to increase from the first day of observation to the third day after treatment. Mortality and paralysis tend to increase with increasing time. The lethal effect of A. reticulata seed extract is very high by reaching 100% at 3 dat (72 hours). The LC95 values of A. reticulata seed extract were 1.89% , 0.49% and 0.36% respectively for analysis times of 1, 2, and 3 hsp. Annona reticulata seed extract has a high insecticidal activity (knock down effect and toxicity) against Callosobruchus maculatus.Extracts from the Annona muricata plant parts are known to have a broad-spectrum insecticidal potential against various species of insect pests. This study aimed to study the bioactive compounds of Annona reticulata fruit extract against Callosobruchus maculatus in the laboratory. The study used five extract treatments that were repeated three times. The treatment consisted of formulations with concentrations of 0.135%, 0.182%, 0.246%, 0.331%, and 0.450%, and controls. The test was carried out by the residual method on the petri dish and tested on the female insect C. maculatus, as well as testing the content of metabolites in the seeds. Phytochemical test results showed that A. reticulata seeds contain alkaloids, phenolics, flavonoids, tannins, steroids, and saponins. The results showed that paralysis already occurred as early as 1 day after treatment (dat) for all given concentrations of the extract, and the death of test insects tended to increase from the lowest concentration to the highest concentration. The mortality of test insects also tends to increase from the first day of observation to the third day after treatment. Mortality and paralysis tend to increase with increasing time. The lethal effect of A. reticulata seed extract is very high by reaching 100% at 3 dat (72 hours). The LC95 values of A. reticulata seed extract were 1.89% , 0.49% and 0.36% respectively for analysis times of 1, 2, and 3 hsp. Annona reticulata seed extract has a high insecticidal activity (knock down effect and toxicity) against Callosobruchus maculatus.